2020
DOI: 10.1186/s13063-020-04406-y
|View full text |Cite
|
Sign up to set email alerts
|

An under-represented and underserved population in trials: methodological, structural, and systemic barriers to the inclusion of adults lacking capacity to consent

Abstract: Background: There is increasing international recognition that populations included in trials should adequately represent the population treated in clinical practice; however, adults who lack the capacity to provide informed consent are frequently excluded from trials. Addressing the under-representation of groups such as those with impaired capacity to consent is essential to develop effective interventions and provide these groups with the opportunity to benefit from evidence-based care. While the spotlight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 49 publications
0
56
0
Order By: Relevance
“…However, a recent review (Shepherd et al, 2019) of UK clinical trials relating to conditions typically affecting mental capacity found that less than 20% included participants who lacked capacity. Shepherd (2020) has also found that many studies report the exclusion of people lacking capacity in a ‘limitations’ section, but rarely attempt to justify this exclusion. In the studies that did provide some explanation of exclusion, Shepherd found that complex legislation and ethical review processes were among the major motivations.…”
Section: Excluding Dementiamentioning
confidence: 99%
“…However, a recent review (Shepherd et al, 2019) of UK clinical trials relating to conditions typically affecting mental capacity found that less than 20% included participants who lacked capacity. Shepherd (2020) has also found that many studies report the exclusion of people lacking capacity in a ‘limitations’ section, but rarely attempt to justify this exclusion. In the studies that did provide some explanation of exclusion, Shepherd found that complex legislation and ethical review processes were among the major motivations.…”
Section: Excluding Dementiamentioning
confidence: 99%
“…Family members can be reluctant to support research activities in care homes if their relative has dementia or if they perceive the research to invade privacy (Lam et al , 2018). In addition, some care home providers may act as “gate keepers”, with the intention of protecting their residents, as there is a general lack of understanding that residents who lack capacity should have equal access to research participation (Shepherd, 2020).…”
Section: Current Evidence Basementioning
confidence: 99%
“…This can be challenging for family members acting as consultee or legal representative, who often experience an emotional and decisional burden as a result [ 10 ]. Concerns about the burden of making proxy decisions, together with broader ethical concerns about who should act as proxy and the ethical basis for their decision, contribute to the methodological, structural, and systemic barriers to the inclusion of adults lacking capacity to consent in trials [ 11 ].…”
Section: Introductionmentioning
confidence: 99%